THE PRINCIPAL'S STRATEGY IN CULTIVATING STUDENTS' DISCIPLINE CHARACTER AT THE INDONESIAN SCHOOL IN KUALA LUMPUR MALAYSIA - Muzakir, Muchammad Ibnu; Fadli, Muhammad Raisul; Miftah Hur Rahman Zh (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to analyze various strategies used by school principals in cultivating students' disciplined character in Indonesian schools in Kuala Lumpur. The research method used was a qualitative study by conducting interviews and observations of several school teachers and principals at Indonesian schools in Kuala Lumpur. The research results show that there are several strategies that are commonly used, including establishing clear school rules, consistent application of sanctions and rewards, involving parents in building student character, and creating a supportive learning environment. The implication of this research is the important role of school principals in shaping students' disciplinary character and the need for comprehensive and consistent implementation of strategies. It is hoped that this research can contribute to the development of character education in Indonesian schools in Kuala Lumpur. The research results show that the principal has a very important role in cultivating the disciplined character of students at school. They use a variety of strategies, including establishing clear school rules, consistent application of sanctions and rewards, involving parents, and creating a supportive learning environment. The implication of this research is the importance of the role of the school principal and the need to implement comprehensive and consistent strategies in shaping students' disciplinary character.